Determination of mechanical properties of materials used for 3D printing - Sedlak, Josef; Chladil, Josef; Cerny, Martin; Polzer, Ales; Varhanik, Matus; Dobrocky, David; Joska, Zdenek; Pokorny, Zdenek (Manufacturing Technology Journal, 2020)
The presented paper deals with determination of mechanical properties of materials used for 3D printing (ABS, nylon and PLA). The theoretical part of the paper characterizes the static tensile test by which selected me-chanical properties of samples were evaluated. The practical part of the paper characterizes the additive technolo-gy Fused Deposition Modelling, by means of which standardized plastic samples were printed on the 3D printer. The practical part also deals with analysis of selected mechanical properties of samples made by Soft Tooling technolo-gy. SG 2000 and SG 145 polyurethane resins were used for the production of samples using Soft Tooling technology. Individual samples were analysed using selected tests (tensile test and hardness test). Surface integrity parameters were also determined for 3D printing test specimens. Parameters (tensile strength, tensile modulus, tensile strength and hardness) that were statistically processed were selected for each test. The paper is finished evaluating the re-sults obtained, which were compared with those given in the material sheets.
Keywords: Mechanical properties; 3D printing; Test specimen; Tensile test; Material